2022
DOI: 10.4014/jmb.2203.03022
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gut in IBD: Intestinal Barrier–Gut Microbiota Interaction

Abstract: The gut microbiota mainly consists of Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, and Inflammatory bowel disease (IBD) is a global disease that is in increasing incidence. The gut, which contains the largest amount of lymphoid tissue in the human body, as well as a wide range of nervous system components, is integral in ensuring intestinal homeostasis and function. By interacting with gut microbiota, immune cells, and the enteric nervous system, the intestinal barrier, which is a solid barrier, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 124 publications
(140 reference statements)
0
18
0
Order By: Relevance
“…Although Axl has been known to act as a negative regulator in the pathogenesis of IBD 18 , to the best of our knowledge, the effect of Axl on changes in the composition of the gut microbiota has not been investigated to date. Previous studies have demonstrated that IBD patients show a reduced abundance of the genera Bacteroides 65 , 66 , Alloprevotella 67 , Odoribacter 68 , Bifidobacterium , Eggerthella 69 , and Olsenella but an increased in Escherichia , Shigella , and Actinobacillus 70 . In addition, the species such as B. vulgatus , B. caccae , B. bifidum , and B. longum 68 are decreased in patients with IBD, whereas the species S. enterica 71 , E. coli 67 , A. segnis , H. parainfluenzae , and E. corrodens 68 are enhanced.…”
Section: Discussionmentioning
confidence: 96%
“…Although Axl has been known to act as a negative regulator in the pathogenesis of IBD 18 , to the best of our knowledge, the effect of Axl on changes in the composition of the gut microbiota has not been investigated to date. Previous studies have demonstrated that IBD patients show a reduced abundance of the genera Bacteroides 65 , 66 , Alloprevotella 67 , Odoribacter 68 , Bifidobacterium , Eggerthella 69 , and Olsenella but an increased in Escherichia , Shigella , and Actinobacillus 70 . In addition, the species such as B. vulgatus , B. caccae , B. bifidum , and B. longum 68 are decreased in patients with IBD, whereas the species S. enterica 71 , E. coli 67 , A. segnis , H. parainfluenzae , and E. corrodens 68 are enhanced.…”
Section: Discussionmentioning
confidence: 96%
“…The more recently available biologics, such as VED and UST, did not seem to show an increased risk of serious infections compared to anti-TNFα agents [ 52 , 53 ]. Additionally, IBD patients had several intrinsic risk factors that play a key role in the development of infections, including malnutrition, surgery, and “leaky gut syndrome”, with consequent increased pathogen exposure and bacterial translocation, especially when co-treated with steroids that could contribute to the observed increase in infection rates [ 54 , 55 , 56 ]. Anti-TNFα agents, particularly ADA, followed by UST and VED, play a role in the onset of dermatological pathologies, including urticaria, erythema, and dermatitis [ 57 ]; moreover, our data showed a higher incidence of malignancies with VED when adjusted on 10 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the contribution of gut microbiota alteration in the pathogenesis of IBD is generally accepted [ 39 , 40 , 41 ]. PA has been reported to be a significant modifier in preventing and restoring gut dysbiosis [ 42 ]; PA is associated with an increase in microflora diversity, an improvement in the development of commensal bacteria, and a beneficial metabolic function [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%